Assessing academic English for higher education admissions - Xiaoming, Xi; Norris, John M. (Innovations in language learning and assessment at ETS, 2021)
"Assessing Academic English for Higher Education Admissions is a state-of-the-art overview of advances in theories and practices relevant to the assessment of academic English skills for higher education admissions purposes. The volume includes a brief introduction followed by four main chapters focusing on critical developments in theories and practices for assessing reading, listening, writing, and speaking, of which the latter two also address the assessment of integrated skills such as reading-writing, listening-speaking, and reading-listening-speaking. Each chapter reviews new task types, scoring approaches, and scoring technologies and their implications in light of the increasing use of technology in academic communication and the growing use of English as a lingua franca worldwide. The volume concludes with recommendations about critical areas of research and development that will help move the field forward. Assessing Academic English for Higher Education Admissions is an ideal resource for researchers and graduate students in language testing and assessment worldwide."